Funding Mechanisms for Civil Society: The Experience of the AIDS Response - Bonnel, René; Rodriguez-García, Rosalía; Olivier, Jill; Wodon, Quentin (Washington, DC: World Bank, 2013)
How resources are being used to fund the community response to human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) is of considerable interest to the donor community and governments. In the past decade, international funding for the HIV and AIDS response provided by governments rose from about US$1 billion to US$8.7 billion; donors increasingly shifted their financial support toward funding community responses to this epidemic. Yet little is known about the global magnitude of these resource flows and how funding is allocated among HIV and AIDS activities and services. Although some studies have been carried out to gather information on the community response by civil society organizations (CSOs), most of them provide only partial information limited to a specific intervention (for example, orphan support) or specific local communities. To address this knowledge gap, the report attempts to answer the following questions: How large is donor funding for community-based interventions that are run by either large nongovernmental organizations (NGOs) or smaller community-based organizations (CBOs)? How do the funds reach various types of CSOs? What are CSOs' other sources of funding, and to what extent are the CSOs dependent on donor funding? How are these funds used for by CSOs? Are there differences among different types of CSOs working on HIV and AIDS?